Effect of Blood Transfusions on the Outcome of Very Low Body Weight Preterm Infants under Two Different Transfusion Criteria - Hsiu-Lin Chen; Hsing-I Tseng; Chu-Chong Lu; San-Nan Yang; Hui-Chen Fan; Rei-Cheng Yang (Elsevier, 2009)
Multiple packed red blood cell (PRBC) transfusions in very low birth weight (VLBW) prematurity have been suggested to be a risk factor for the development of retinopathy of prematurity (ROP) or for chronic lung disease (CLD). The purpose of this study was to examine the effect of PRBC transfusions on the outcome of VLBW prematurity. Methods: In total, between July 2005 and June 2006, 36 VLBW preterm babies were admitted to our neonatal intensive care unit and were randomly allocated to the "restrictive" (n = 19) or "liberal" (n = 17) criteria for PRBC transfusion. Complete blood count (CBC) was examined at admission and 30 days later. Reticulocyte counts, serum iron and ferritin were examined and compared with the clinical outcomes. Results: Infants in the liberal group received a larger PRBC transfusion volume compared with the restrictive group over 30 days (41.7 ± 20.1 vs. 27.2 ± 15.9 mL, p = 0.029). There were no significant differences in the proportion of patients with respiratory distress syndrome, patent ductus arteriosus, severe intraventricular hemorrhage, ROP or CLD between the two groups. The laboratory data, except reticulocyte count, showed no significant difference on day 30. Further analysis of premature babies with and without CLD showed that total transfused blood volume greater than 30 mL over 30 days was a risk factor for developing CLD in VLBW infants. Conclusion: Both criteria of PRBC transfusion had similar clinical outcomes, although liberal transfusion resulted in a greater amount of blood transfused and a low reticulocyte count at 30 days of age. We suggest restrictive criteria for minimizing the overall amount of transfusion to less than 30 mL may be a better way of preventing CLD in VLBW infants.